Performance of Asymmetric Propellers under Varying Blade Spacing - Usov, D.; Chronis, T.; Filippone, A. (My University, 2023)
This paper investigates the performance of two-bladed, radially asymmetric propellers with uneven blade spacing during axial flight. The study’s objective is to analyse the impact of blade spacing on thrust, power, and propulsive efficiency in a two-bladed asymmetric propeller. To achieve this, three asymmetric propellers were simulated using the free-vortex wake method, varying blade spacing from 30 to 90 degrees. The study compared the outcomes of the simulations to those of a reference propeller to identify any possible varia-tions in performance. The results indicated only a slight change in overall propeller performance. It was de-termined that the marginal deterioration in the performance of the propeller was the consequence of the aer-odynamic interference effects between the blades, which ultimately offset each other. Therefore, if such pro-peller geometries offer benefits beyond performance, it is sensible to utilise them.
Keywords: Aerodynamics